Considering soil C information in decision-making - Luedeling, Eike (2017)
Considering soil C information in decision-making by Eike Luedeling, World Agroforestry Center and University of Bonn, Germany. Presentation made at Soil Carbon Sequestration: Supporting NDCs and donor action. A CGIAR-wide workshop held 12 Nov 2017 at ZEF Center for Development Research, University of Bonn. Workshop organized jointly by: CGIAR Research Programs on Climate Change, Agriculture and Food Security (CCAFS); Water, Land and Ecosystems (WLE) and Forests, Trees and Agroforestry (FTA).